Legality of the Position of Advocates as Reporting Parties in the Prevention and Eradication of Money Laundering Crimes - Martina Nilamsari; I Made Wirya Darma (Dinasti Research, 2024)
A mortgage aims to provide protection and legal certainty for stakeholders, one of which is the mortgage-holding creditor. However, in practice, this goal has not been fully realized, as existing mortgages can still be annulled by the court. Debtors must still be held accountable if the collateral bound by the mortgage is annulled by the court, such as for expenses already incurred by the creditors and for the loss of expected profits from the loan. Another effort creditors can make to reclaim their prioritized rights from the debtor is to require the debtor to replace the collateral annulled by the court with another asset of equal nominal value, and then impose a new mortgage on the replacement asset, such as in the form of a mortgage, fiduciary, hypothec, or pledge.